Effects of crude glycerin on ruminal metabolism and diet digestibility of flaked-corn finishing diets - G.L. Parsons; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Expansion of the biodiesel industry has increased supplies of crude glycerin available for livestock feeding. Catalyzed reactions between methanol and triglycerides from vegetable oils, such as soybean oil, yield biodiesel and a coproduct, crude glycerin. Approximately 10% of the weight of soybean oil used to produce biodiesel becomes glycerin. Limited work has been conducted to understand metabolism of glycerin in ruminant livestock. In previous studies at Kansas State University, feeding crude glycerin at 8% or less of the diet improved cattle performance. Subsequent laboratory experiments indicated that low levels of glycerin may improve ruminal fermentation. This study was conducted to determine whether adding low levels of glycerin to feedlot diets could affect diet digestibility.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Crude glycerin; Metabolism; Digestibility; Flaked-Corn